SHARIA-BASED BUMDES MANAGEMENT AS AN ALTERNATIVE FOR COMMUNITY MICRO ENTERPRISE EMPOWERMENT: NORTH ACEH DISTRICT, LHOKSEUMAWE CITY AND BIREUN DISTRICT - Likdanawati; Hamdiah; Rico Nur Ilham; Frengki Putra Ramansyah; Muhammad Multazam (International Conference on Health Science, Green Economics, Educational Review and Technology, 2024)
The government program, namely by providing a budget for community empowerment, is used to support the capital for the establishment of Village-Owned Enterprises (BUMDes).The population of this study was all BUMDes Managers in North Aceh Regency, Lhokseumawe City and Bireun Regency, totaling 52 BUMDes Leaders, all of whom were used as research samples. The results of this study are that human resources have a positive and insignificant effect on improving the village economy in BUMDes Managers. BUMDes Manager Strategy has a positive and significant effect on improving the village economy in BUMDes Managers. Regional Autonomy has a negative and insignificant effect on improving the village economy in BUMDes Managers. Besic Potential moderates the effect of human resources on improving the village economy in BUMDes Managers. Besic Potential does not moderate the effect of BUMDes Manager Strategy on improving the village economy in BUMDes Managers. Besic Potential moderates the effect of Regional Autonomy on improving the village economy in BUMDes Managers